The effect of grain size on the twin initiation stress in a TWIP steel. (1st May 2015) - Rahman, K.M.; Vorontsov, V.A.; Dye, D.
Abstract: The influence of grain size on the twinning stress of an Fe–15Mn–2Al–2Si–0.7C Twinning Induced Plasticity (TWIP) steel has been investigated. Five grain sizes were obtained using a combination of cold rolling and annealing. Electron backscatter diffraction (EBSD) analysis revealed that the material exhibited a typical cold rolled and annealed texture. Tensile testing showed the yield stress to increase with decreasing grain size, however, the ductility of the material was not substantially affected by a reduction in grain size. Cyclic tensile testing at sub-yield stresses indicated the accumulation of plastic strain with each cycle, consequently the nucleation stress for twinning was determined. The twin stress was found to increase with decreasing grain size. Furthermore, the amount of strain accumulated was greater in the coarser grain material. It is believed that this is due to a difference in the twin thickness, which is influenced by the initial grain size of the material. SEM and TEM analysis of the material deformed to 5% strain revealed thinner primary twins in the fine grain material compared to the coarse grain. TEM examination also showed the dislocation arrangement is affected by the grain size. Furthermore, a larger fraction of stacking faults was observed in the coarse-grained material. It is concluded that the twin nucleation stress and also the thickness of the deformation twins in a TWIP steel, is influenced by the initial grain size of the material. In addition grain refinement results in a boost in strength and energy absorption capabilities in the material.